Flow invariant droplet formation for stable parallel microreactors - Carson T. Riche (Nature Portfolio, 2016)
Microfluidic reactors offer cheap and simple solutions for nanoparticle synthesis, but suffer from the variation in particle size due to flow fluctuations. Riche et al. fabricate a device that is robust over a large range of flow rates and enables consistent particle synthesis in parallel operation.